A full understanding of oxygen reduction reaction mechanism on Au(1 1 1) surface. (7th August 2017) - Yang, Yang; Dai, Changqing; Fisher, Adrian; Shen, Yanchun; Cheng, Daojian
Abstract: Oxygen reduction and hydrogen peroxide reduction are technologically important reactions in energy-conversion devices. In this work, a full understanding of oxygen reduction reaction (ORR) mechanism on Au(1 1 1) surface is investigated by density functional theory (DFT) calculations, including the reaction mechanisms of O2 dissociation, OOH dissociation, and H2 O2 dissociation. Among these ORR mechanisms on Au(1 1 1), the activation energy of O 2 ∗ hydrogenation reaction is much lower than that of O 2 ∗ dissociation, indicating that O 2 ∗ hydrogenation reaction is more appropriate at the first step than O 2 ∗ dissociation. In the following, H2 O2 can be formed with the lower activation energy compared with the OOH dissociation reaction, and finally H2 O2 could be generated as a detectable product due to the high activation energy of H2 O2 dissociation reaction. Furthermore, the potential dependent free energy study suggests that the H2 O2 formation is thermodynamically favorable up to 0.4 V on Au(1 1 1), reducing the overpotential for 2 e − ORR process. And the elementary step of first H2 O formation becomes non-spontaneous at 0.4 V, indicating the difficulty of 4 e − reduction pathway. Our DFT calculations show that H2 O2 can be generated on Au(1 1 1) and the first electron transfer is the rate determining step. Our results show that gold surface could be used as a good catalyst for small-scale manufacture and on-site production of H2 O2 .